Determination of indications for the choice of the preparation method of the root canal system with rotation and reciprocation instruments - I. V. Pyatkova (Эндодонтия Today, 2020)
Compliance with the algorithms of endodontic treatment in most cases ensures the quality of treatment. However, real, long-term and sometimes immediate results that occur in clinical practice are not always successful. In general, the main reason for the unfavorable outcome of dental treatment is an incomplete sanitation of the root canal system. Modern publications by J. F. Siqueira, I. N. Rocas, and D. Ricucci (2019) note that many issues of endodontic treatment are unresolved. It follows that improving the quality of endodontic treatment is still relevant.Aim. To compare two systems of instruments for root canal preparation with different types of rotation.Materials and methods. To identify a tool that will increase the efficiency of root canal preparation, taking into account their anatomy using CBCT, 24 teeth were removed, taken according to orthodontic or pristidintic indications, without previous endodontic treatment. Among them there were 2 incisors, 1 canine, 6 premolars, 15 molars. In total, 60 canals were examined.Results. The shape changes throughout the canal, turning into a round, oval, slit-like, complementing the configuration by the isthmuses between the canals in 13.3% of cases. WaveOne Gold showed a change in cross-sectional shape after preparation, while ProTaper Universal retained a rounded section of 6.67% after preparation of the slit-like channels.Conclusion. Identified priority technique of root canal preparation, allowing to reduce the number of instruments and, as a consequence, the possibility of technological failures in the root canal to reduce machining of the mouth of the channel, retaining dentine playing a major role in the further prosthesis and positive prediction of remote results.